2014
DOI: 10.1016/j.ijfatigue.2013.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Propensities of crack interior initiation and early growth for very-high-cycle fatigue of high strength steels

Abstract: Fatigue tests of a high carbon chromium steel were performed using rotating bending and ultrasonic axial cycling. Fatigue crack initiated at specimen interior for very-high-cycle fatigue (VHCF) with fish-eye pattern embracing fine-granular-area (FGA) originated from inclusion. The fatigue life from FGA to fish-eye and from fish-eye to the critical crack size was respectively calculated, so as to estimate the fatigue life contributed by FGA. The crack extension rate within FGA was also estimated. Our results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
173
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 200 publications
(188 citation statements)
references
References 29 publications
13
173
1
1
Order By: Relevance
“…A couple of statements have been made regarding the FGA formation: (1) FGA is accompanied by VHCF crack initiation from interior inclusion for high carbon steels [29], (2) FGA consumes more than 90 percent of VHCF life [12,14,17], and (3) FGA is finished when the plastic zone size of the microcrack exceeds the width of the martensite [21]. Here, we further assume that dislocations are piled up along the slip band in the martensite as described by the Tanaka-Mura model [30,31], and take into account the influence of tensile strength and FGA size on VHCF crack initiation life.…”
Section: Dominant Variable Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A couple of statements have been made regarding the FGA formation: (1) FGA is accompanied by VHCF crack initiation from interior inclusion for high carbon steels [29], (2) FGA consumes more than 90 percent of VHCF life [12,14,17], and (3) FGA is finished when the plastic zone size of the microcrack exceeds the width of the martensite [21]. Here, we further assume that dislocations are piled up along the slip band in the martensite as described by the Tanaka-Mura model [30,31], and take into account the influence of tensile strength and FGA size on VHCF crack initiation life.…”
Section: Dominant Variable Sensitivity Analysismentioning
confidence: 99%
“…Surface defects may become non-propagating cracks [12], and sometimes grain boundary could also become a crack origin for high carbon chromium steel under low tempering temperature [5,13]. It is also revealed that fatigue crack initiation within FGA is dominated for high cycle fatigue (HCF) and VHCF, and FGA consumes more than 90% fatigue life [14,15]. Thus, microstructure barriers near the fatigue crack origin are responsible for crack initiation and determine the fatigue life scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue strength of 1 × 107 cycles is usually defined as the fatigue limit. All specimens were tested at room temperature at a frequency of 6000 r/min and under load control at stress ratios R = −1, and the regarded load was taken as the control variable [13][14][15]. The dimensions of fatigue specimens are shown in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the stress intensity factor range at the front of the FGA was a constant and was close to the threshold value of the crack propagation K th . In crack initiation and early growth stage of VHCF, the crack growth rate is much lower than 10 −10 m/cycle [13,[17][18][19][20], and more than 90 % of fatigue life is consumed to form the FGA [21][22][23][24][25]. Therefore, it is essential to develop a model to predict the fatigue life in relation to FGA.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al [25] developed the dislocation model proposed by Tanaka and Mura [32]. By introducing a fraction of an irreversible dislocation, the number of cycles related to crack initiation N i at inclusion was expressed as:…”
Section: Introductionmentioning
confidence: 99%